2021
DOI: 10.3390/jcm10132760
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coronal Preflaring on the Accuracy of Electronic Working Length Determination: Systematic Review and Meta-Analysis

Abstract: Aim. To conduct a systematic review and meta-analysis according to the following PICO question: in extracted human permanent teeth, does preflaring, compared with unflared canals, influence the accuracy of WL determination with EAL? Material and Methods. A systematic review was conducted according to the PRISMA checklist, using the following databases: PubMed, Science Direct, Scopus, and Web of Science. Studies related to WL determination using EAL both in preflared and unflared root canals of extracted human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…O preparo prévio do terço cervical permite que o instrumento chegue à região apical de forma mais livre, aumentando a precisão na leitura do localizador. 2,18,19 Melo et al 20 (2020) testaram 3 aparelhos LFE em três diferentes situações: sem preparo cervical prévio, com preparo realizado com instrumento #25.06 (preparo conservador) e com preparo utilizando instrumento #25.12 (preparo convencional). Embora os aparelhos testados tenham apresentado precisão satisfatória mesmo quando o preparo cervical não foi realizado, o preparo cervical convencional aumento de forma significante a precisão de todos os aparelhos.…”
Section: Discussionunclassified
“…O preparo prévio do terço cervical permite que o instrumento chegue à região apical de forma mais livre, aumentando a precisão na leitura do localizador. 2,18,19 Melo et al 20 (2020) testaram 3 aparelhos LFE em três diferentes situações: sem preparo cervical prévio, com preparo realizado com instrumento #25.06 (preparo conservador) e com preparo utilizando instrumento #25.12 (preparo convencional). Embora os aparelhos testados tenham apresentado precisão satisfatória mesmo quando o preparo cervical não foi realizado, o preparo cervical convencional aumento de forma significante a precisão de todos os aparelhos.…”
Section: Discussionunclassified
“…This coincides with the results of Pegum Unsal Peker et al, who concluded that Raypex 6 is not influenced by irrigation solutions because of its multifrequency technology, which shows precise WL results. 9,37 The 6 th generation apex locator is believed to be less sensitive to external factors that increase measuring reliability, 38 such as the number and taper of the files used in coronal pre-flaring, which may influence the enlargement of the coronal portion of the canal. 39 The sixth generation EALs have been proven to have a preliminary determination of canal moistness, and based on the constant determined moisture, the sixth-generation EALs adapt the measuring method for either a dry or wet root canal environment.…”
Section: Discussionmentioning
confidence: 99%
“…4 Flaring the cervical third of the root also improves its medium and apical third cleaning 5,6 and reduces the amount of debris that could be extruded from the apical foramina 7,8 and also a flare-up incidence. 4,9 Cervical preflaring may also reduce the instrument fracture incidence 10,11 and allow a more precise electronic odontometry performance, [12][13][14] given that the endodontic file could be better adjusted to the apical third of the root. [15][16][17] Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%